Optical Imaging of Integrin αβ Expression with Near-Infrared Fluorescent RGD Dimer with Tetra(ethylene glycol) Linkers - Zhaofei Liu; Shuanglong Liu; Gang Niu; Fan Wang; Shuang Liu; Xiaoyuan Chen (Molecular Imaging)
Integrin α v β 3 plays great roles in tumor angiogenesis, invasion, and metastasis. We report here the noninvasive visualization of tumor integrin α v β 3 expression by using near-infrared fluorescence (NIRF) imaging of an IRDye800-labeled new cyclic RGD (arginine-glycine-aspartic acid) dimer with tetra(ethylene glycol) (PEG 4 ) linkers (ie, E[PEG 4 -c(RGDfK)] 2 , PEG 4 = 15-amino-4,7,10,13-tetraoxapentadecanoic acid) in a U87MG tumor model. Fluorescent dye–labeled E[PEG 4 -c(RGDfK)] 2 were subjected to in vitro cell staining, in vivo NIRF imaging, ex vivo NIRF imaging, and histologic studies. The in vitro and in vivo characterization of dye-labeled E[PEG 4 -c(RGDfK)] 2 were compared with dye-labeled RGD dimer without PEG 4 linkers (namely, E[c(RGDfK)] 2 ). Both Cy5.5-E[PEG 4 -c(RGDfK)] 2 and Cy5.5-E[c(RGDfK)] 2 exhibited integrin α v β 3 binding specificity in a cell-staining experiment. In vivo NIRF imaging showed higher tumor accumulation and tumor to background contrast of IRDye800-E[PEG 4 -c(RGDfK)] 2 over IRDye800-E[c(RGDfK)] 2. The tumor integrin α v β 3 specificity of IRDye800-E[PEG 4 -c(RGDfK)] 2 was confirmed by successful inhibition of tumor uptake in the presence of an excess dose of c(RGDfK). Histologic examination revealed both tumor vasculature and tumor cell integrin α v β 3 binding of IRDye800-E[PEG 4 -c(RGDfK)] 2 in vivo. In summary, NIRF imaging with IRDye800-E[PEG 4 -c(RGDfK)] 2 offers an easy, fast, and low-cost way to detect and semiquantify tumor integrin α v β 3 expression in living subjects.